Is cook 'der Koch' or 'die Köchin'? Problems of (social) gender in translation - Nissen, Uwe Kjær (HERMES - Journal of Language and Communication in Business, 2017)
By means of the category of gender, especially the concept of social gender, this article intends to illustrate the different parameters that are involved when referring to translation as a “crosscultural transfer”. Specific factors that have an influence on the translation, such as connotations of gender, pragmatic situations, different linguistic structure (i.e. languages that show grammatical vs. languages that show pronominal gender), are discussed. The article emphasizes the importance of the translator’s role to interpret the source text and to determine the function of the target text.